Studentische Forschung im Praxissemester Fallbeispiele aus der Lehrkräftebildung - Beckmann, Timo; Ehmke, Timo; Besser, Michael (Verlag Julius Klinkhardt, 2022)
This anthology presents successful examples of "research work" by teacher education students. Seminar concepts from the fields of natural sciences, music, educational science, mathematics and art, applied social psychology and the subject of German are presented. The volume is framed by a comprehensive theoretical introduction to the concept of research-based learning and its implementation at Leuphana University Lüneburg.